2021
DOI: 10.3389/fmicb.2021.713724
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Genomic Surveillance of Virulence Factors in Shiga Toxin-Producing Escherichia coli in New South Wales, Australia

Abstract: The disease caused by Shiga toxin-producing Escherichia coli (STEC) remains a significant public health challenge globally, but the incidence of human STEC infections in Australia remains relatively low. This study examined the virulence characteristics and diversity of STEC isolates in the state of New South Wales between December 2017 and May 2020. Utilisation of both whole and core genome multi-locus sequence typing (MLST) allowed for the inference of genomic diversity and detection of isolates that were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 82 publications
(161 reference statements)
1
6
0
Order By: Relevance
“…We showed that within our dataset, STEC of lower pathogenic potential were in circulation. This observation is consistent with the trend previously observed at the pre-lockdown period, both at the national or the state level, which showed that most clinical STEC had lower pathogenic potential (17, 7075).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We showed that within our dataset, STEC of lower pathogenic potential were in circulation. This observation is consistent with the trend previously observed at the pre-lockdown period, both at the national or the state level, which showed that most clinical STEC had lower pathogenic potential (17, 7075).…”
Section: Discussionsupporting
confidence: 92%
“…Prior to the COVID-19 border closures, it was reported that STEC isolated from clinical sources in NSW predominantly harboured stx genes of lower pathogenic potential (17). The COVID-19 lockdown provided an opportunity to interrogate the pathogenic potential STEC landscape without external influences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations